Challenges Faced by Teachers in Addressing Achievement Gaps of Students at Nyumba Yanga Secondary School in Zambia - Alinjavwa Simbeye; Pethias Siame (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Persistent academic achievement gaps among students from diverse socioeconomic and cultural backgrounds continue to challenge educators. Teachers, positioned at the forefront of efforts to promote educational equity, often encounter numerous obstacles in addressing these disparities and meeting the diverse needs of their students. Understanding these challenges is essential for developing targeted interventions and policy reforms to help narrow achievement gaps. This study aims to explore the primary challenges teachers face in addressing academic disparities and to identify strategies and support systems that could empower them in their efforts to bridge these gaps. Guided by social justice education and culturally responsive teaching frameworks, this study emphasizes addressing systemic inequities, incorporating students’ cultural and linguistic backgrounds, and recognizing teachers as agents of change. Employing a qualitative approach, the study gathered data through semi-structured interviews with teachers to gain insight into their experiences and perceptions and to understand the prevalence and nature of these challenges. The findings reveal complex challenges related to classroom diversity, resource limitations, professional development, systemic barriers, and emotional factors. The study also highlights strategies and support systems that teachers view as crucial for empowering them to reduce achievement gaps and promote educational equity, such as culturally responsive teaching, educational equity, and social justice education.